Assessment of thyroid function status in transfusion dependent thalassemic children - Mazumder, Abul Basher M. Osman Hayder; Begum, Suraiya; Parvin, Roksana; Akter, Salma; Shanta, Sumya Afrin (International Journal of Contemporary Pediatrics, 2022)
Background: Frequent blood transfusions have been associated with serum iron overload, which may result in hypothyroidism and other endocrine abnormalities in transfusion dependent thalassemic patients. Thyroid dysfunction has been reported in a number of studies on these pts. The aim of the study is to assess the thyroid function status among the transfusion dependent thalassemic children. Methods: This was a cross sectional study conducted in the department of transfusion medicine, department of Pediatric hematology and oncology and department of hematology, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka for a period of 18 months. A total number of 86 children with transfusion dependent thalassemia who met the inclusion and exclusion criteria were studied. Demographic data as well as history of blood transfusion and chelation therapy were collected. Thyroid function and iron load status were evaluated by measuring serum FT4, TSH and ferritin levels. Results: Out of 86 thalassemia patients, euthyroid patients were 77 (89.5%) and hypothyroid patients were 9 (10.5%). Eight (9.3%) patients were compensated and 1 (1.2%) was uncompensated hypothyroidism. Statistically significant association was found between number of blood transfusion and serum ferritin level (≥2000 ng/ml) with development of hypothyroidism in thalassemic patients. Mean ferritin level was higher in hypothyroid (4797.8±2027.4 ng/ml) group than in euthyroid (3628.8±2448.5 ng/ml) groups. Conclusions: Frequency of hypothyroidism was 10.5% (compensated 9.3% and uncompensated 1.2%). Number of blood transfusion and ferritin level were found significantly associated with the development of hypothyroidism in thalassemic patients.